ANALISIS GAYA BAHASA PERTENTANGAN DALAM NOVEL SENJA DAN PAGI KARYA ALFFY REV DAN LINKA ANGELIA (TINJAUAN iSTILISTIKA) - Asriyani; Maliudin (Program Studi Sastra Indonesia Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
This research is a qualitative descriptive research thataim to describe the language style of opposition in Senja dan Pagi novels by Alffy Rev and Linka Angelia using a stylistic review. As research material, then listened in its entirety to the contents of Alffy Rev and Linka Angelia’s Senja dan Pagi Novels so as to find sentences that contain contradictory langue style in them. In analyzing the data, the researcher used an objective approach used in order to examine the style of language used by novel writers contained in the novel Senja dan Pagi by Alffy Rev And Linka Angelia found 65 data. Namely is the form of 30 data of hyperbole, 4 data of litotes,4 data of oxymoron, 4 data of sylepsis, 1 data of satire, 2 data of inuendo, 2 data of paradox, 13 data of climax, 1 data of anticlimax, 1 data of prosteron hysteron and 1 data of cynicism. Keyword: Stylistics, contradictory language style, Novel.